Social Entrepreneurship as part of Social Policies from the Islamic Perspective - Efe, Ahmet (Bartın Üniversitesi, 2017)
Practices related with social policies and social entrepreneurs are formed and applied with the light of western best practices. In this study, with an approach of İslamic point of view, the underpinning basis of İslamic economics related to social entrepreneurships are being searched. Particularly in setting up of economic principles with their basis from the holy Koran is being searched in brief with some specimens and comparisons with western practices. Our argument is that since basics of Islamic economics on social entrepreneurship are valid and pervasive and its results can be more congruent, sustainable, logical and beneficial in providing human happiness and easing burden of worldly life. Therefore, in comparing western practice that centralizes worldly life in primer focus by subjugating everything that can serve material progress and capital accumulation as means of production or productive relations, with İslamic economics that takes world only as a temporary place but worthwhile to the extent that it preserves life of the hereafter by subjugating whatever exist as creature means relation of which should be based on Divine consent. Therefore wielding new methods and approaches within İslamic tradition and virtue, social entrepreneurship can produce more positive and sustainable results in comparison with a secular and materialistically rent seeking backed and positivistic approach.

Son zamanlarda favori konular arasına giren sosyal girişimcilik ile ilgili politika ve uygulamalar daha çok merkez batı ülkelerinden esinlenerek oluşturulmaktadır. Bu çalışmamızda İslami bakış açısıyla İslam ekonomisinin sosyal girişimcilik ile ilgili temelleri incelenmektedir. İddiamız, İslam'ınevkaf gibi sosyal girişimcilik noktasındaki uygulamalarının başarılı tarihsel örnekleriyle mevcut olduğu ve geçmişteki iyi uygulamalardan hareketle daha tutarlı, mantıklı ve yararlı sonuçlar doğurabildiğidir. Ekonomi, sosyal politika ve İslam dini çerçevesinde yapılan analizlerde İslam'ınsosyal girişimciliği tesis etmedeki orijinalliği özet olarak ortaya konulmaktadır. Buna göre, dünya hayatını merkeze alarak diğer her şeyi dünyadaki maddi kazanımlar açısından araçsallaştıran batı kapitalizminin sosyal girişimcilik yaklaşımına nazaran geçici dünya hayatını ve bütün gereklerini ebedi olan ahiret hayatını kazanmak için bir araç olarak görüp her iki hayata da değerleri kadar önem vererek dünyevi varlıkların seferberliğini sağlayan İslami içtimai teşebbüs yaklaşımın üstünlüğü savunulmaktadır. Bu noktada her türlü yeni gelişmeden istifade etmeye ve yenilikçiteknik araçları kullanmaya olanak sağlanırken imanın gereğini ve ihlası koruma noktasında niyetlere ve yaklaşımlara özel önem verilmesi gerektiği önerilmektedir.
İslam'da Sosyal Politika Kapsamında Sosyal Girişimciliğin Değerlendirmesi